Suggested application of HER2+ breast tumor phenotype for germline TP53 variant classification within ACMG/AMP guidelines. Issue 9 (12th June 2020) - Fortuno, Cristina; Mester, Jessica; Pesaran, Tina; Weitzel, Jeffrey N.; Dolinsky, Jill; Yussuf, Amal; McGoldrick, Kelly; Garber, Judy E.; Savage, Sharon A.; Khincha, Payal P.; Gareth Evans, D.; Achatz, Maria Isabel; et al.
Abstract: Early onset breast cancer is the most common malignancy in women with Li‐Fraumeni syndrome, caused by germline TP53 pathogenic variants. It has repeatedly been suggested that breast tumors from TP53 carriers are more likely to be HER2+ than those of noncarriers, but this information has not been incorporated into variant interpretation models for TP53 . Breast tumor pathology is already being used quantitatively for assessing pathogenicity of germline variants in other genes, and it has been suggested that this type of evidence can be incorporated into current American College of Medical Genetics and Genomics/Association for Molecular Pathology (ACMG/AMP) guidelines for germline variant classification. Here, by reviewing published data and using internal datasets separated by different age groups, we investigated if breast tumor HER2+ status has utility as a predictor of TP53 germline variant pathogenicity, considering age at diagnosis. Overall, our results showed that the identification of HER2+ breast tumors diagnosed before the age of 40 can be conservatively incorporated into the current TP53 ‐specific ACMG/AMP PP4 criterion, following a point system detailed in this manuscript. Further larger studies will be needed to reassess the value of HER2+ breast tumors diagnosed at a later age. Abstract : This article presents a review of published studies and analysis of age‐level data from individuals undergoing multigene panel testing and confirms that HER2+ breast tumor status is overrepresented patients with TP53 pathogenic variants, in particular patients with early onset cancer. This study also proposes a strategy to use this information within ACMG/AMP guidelines as evidence toward TP53 variant pathogenicity.